AB0719 2-Year Incidence of New Immune-Mediated Inflamatory Diseases in Patients with Spondyloarthritis. the Aquiles Study. (10th June 2014) - García-Vicuna, R.; Zarco, P.; Gonzalez, C.M.; Rodríguez de la Serna, A.; Peiro, E.; Mateo, I.; Linares, L.; Calvo, J.; Fernandez, S.; Cea-Calvo, L.; Arteaga, M.J.; Marín-Jiménez, I.; et al.
Abstract : Background: Patients with spondyloarthritis (SpA) frequently show other immune-mediated inflammatory diseases (IMID) Objectives: To describe the 2-year incidence of new diagnoses of IMID in patients with SpA recruited for the AQUILES study Methods: AQUILES was a prospective observational study on 3 independent cohorts of patients aged ≥18 years-old with SpA, inflammatory bowel disease (IBD) or psoriasis recruited from rheumatology, IBD and dermatology offices from 15 hospitals in Spain. Patients were followed for 2 years. In the SpA cohort, the diagnosis of new IMID was based on reports from gastroenterologists (IBD), dermatologists (psoriasis) or ophthalmologists (uveitis) Results: A total of 513 patients with SpA completed the 2-year follow-up (mean age: 48 years-old; 37.5% females, 62.5% males). Median duration of disease was 7.8 years. The diagnoses at baseline were: ankylosing spondylitis (AS) (n=285), psoriatic arthritis (PsA) (n=130), enteropathic arthritis (n=13), undifferentiated arthritis (n=83) and others (n=2). At baseline, 45% had other IMID (4.9% IBD; 28.7% psoriasis; 14.6% uveitis). During the 2-year period, 22 new diagnoses of incident IMID were recorded (cumulative incidence: 4.3%, 95% CI: 2.4-6.1; incidence rate: 17 cases per 10, 000 patients-year). The predominant incident IMID was uveitis (16 cases, cumulative incidence 3.1%, 95% CI: 1.5-4.7). In the subgroup with AS, there were 16 new cases of IMID (5.6%; 13 of them uveitis [4.6%], 1 IBD [0.4%] and 2 psoriasis [0.8%]). In patients with PsA only 2 patients developed a new IMID (2 new diagnoses of psoriasis [1.5%]). In those with undifferentiated SpA, there were 2 new diagnoses of uveitis (2.4%) and 1 psoriasis (1.2%), and 1 patient with enteropathic arthritis developed uveitis. There were no differences in the incidence by patient's age, gender, duration of disease, extra-articular manifestations or family history of SpA, and the multivariate analysis identified the diagnosis of AS as the only predictor of development of new IMID (OR: 3.5 [1.0-15.3, p=0.049] versus psoriatic arthritis) Conclusions: In SpA patients recruited for the AQUILES study, the 2-year cumulative incidence of new IMID was 4.3%, mostly due to new patients with diagnosis of uveitis in patients with AS. Diagnosis of AS at baseline was the only predictor for the development of a new IMID Acknowledgements: The AQUILES study was funded by Merck Sharp & Dohme of Spain. The authors thank the investigators for the recruitment and follow-up of patients Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3090